Cities of Slovenia tomorrow according to regional development plans - Kušar, Simon (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2004)
Regional planning is one of factors that influence the future development of cities. In Slovenia, regional development plans, which consist of regional development programs and subprograms, are in preparation for the time period that runs up to 2006. These programs shall have an important influence to the future functions of cities, their morphological structure, functional role and social processes within them. Additionally, regional and subregional centres may gain on their importance. Cities of Slovenia shall develop in accor-dance with the paradigm of sustainable development.
Keywords: mesta; urbani razvoj; regionalno planiranje; regionalni razvoj; Slovenia; Slovenija